Pengaruh Kebijakan Dividen, Kebijakan Hutang dan Good Corporate Governance terhadap Nilai Perusahaan yang Terdaftar di Jakarta Islamic Index Periode 2014-2016 - Martini, Tina; Sunarto, S. (IAIN Kudus, 2018)
This study aims to empirically examine the effect of dividend policy, debt policy, and good corporate governance on the value of companies listed in the Jakarta Islamic Index for the 2014-2016 period. This type of research is field research, which is conducting research in the field to obtain data or information directly. Data collection techniques using the documentation method. The data analysis technique used is descriptive analysis, multiple regression analysis, partial t test and coefficient of determination. The results showed that the dividend policy variable had a significant positive effect on firm value, the debt policy variable has a significant positive effect on firm value, the variables of good corporate governance do not affect the value of the company.